Care management for sick toddlers through integrated management of childhood illness approach - Hendayani, Siti Nur Endah; Nurhayati, Fitri (Institute of Computer Science (IOCS), 2024)
Efforts to promote child health aim to reduce the mortality rate of newborns, infants, and toddlers. One way to decrease the mortality rate among children under five is by enhancing the skills of healthcare workers in providing care through the Integrated Management of Childhood Illness approach. Implementing this approach effectively and on a wider scale can be cost-effective and significantly contribute to reducing the death rate among neonates, infants, and children under five. The aim of this study is to provide care management for sick toddlers through integrated management of childhood illness approach. This study is a case study that employs a descriptive observational method to examine the application of the Integrated Management of Childhood Illness approach. The subject of the case study is a 4-year 8-month old toddler. The study took place at PMB Siti Nuraeni in September 2023. Data was collected directly (primary data) using the Varney management approach and documented using the SOAP format (subjective data assessment, objective data assessment, data analysis, and case management). The collected data was then analyzed using descriptive analysis. The study concludes that data analysis is conducted by assessing subjective and objective data of a 4-year-8-month-old toddler, who has a cough but no pneumonia. The care for subject, is provided in line with the Integrated Management of Childhood Illness approach. The study recommends that midwives should be able to observe and detect early signs of danger that may occur during the growth and development of toddlers.